EXAMINING THE WAYS ENGLISH LANGUAGE TEACHERS USE METADISCOURSE TO SCAFFOLD LEARNING AND SUPPORT STUDENT COMPREHENSION - Putra, Fahry Rizaldy; Saputri, Yasinta Eka (Journal of Educational Learning and Innovation (ELIa), 2023)
Metadiscourse, or language that is used to reflect on or comment on the content of a message, plays a critical role in the development of student comprehension and learning in the English language classroom. This paper investigates the ways in which English language teachers use metadiscourse to scaffold learning and support student comprehension. The paper employs a qualitative analysis of lesson transcripts, interviews with teachers, and observations of classroom interactions to identify the types of metadiscourse that are used and the ways in which they are used to guide student learning. The results of the paper highlight the importance of metadiscourse in pedagogical discourse, and provide insights into the ways in which teachers can effectively use metadiscourse to support student learning in the English language classroom.